2000
DOI: 10.1037/0882-7974.15.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Is age-related stability of subjective well-being a paradox? Cross-sectional and longitudinal evidence from the Berlin Aging Study.

Abstract: Subjective well-being is thought to remain relatively stable into old age despite health-related losses. Age and functional health constraints were examined as predictors of individual differences and intraindividual change in subjective well-being, as indicated by positive and negative affect, using cross-sectional (N = 516) and longitudinal (N = 203) samples from the Berlin Aging Study (age range 70-103 years). In cross-sectional and longitudinal analyses, age and functional health constraints were negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
391
5
9

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 559 publications
(448 citation statements)
references
References 55 publications
43
391
5
9
Order By: Relevance
“…For example, it could be shown that a comparatively large number of studies have been carried out on cognitive and affective (above all, negative) SWB, whereas there has been markedly less research on other components of well-being such as social but also positive affective SWB. This is surprising when it is considered that it is particularly positive affective SWB that seems to decline with growing age (see [36]). Hence, when considering this domain of SWB, it would be particularly worthwhile to study the potential of exercise to bring about change.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, it could be shown that a comparatively large number of studies have been carried out on cognitive and affective (above all, negative) SWB, whereas there has been markedly less research on other components of well-being such as social but also positive affective SWB. This is surprising when it is considered that it is particularly positive affective SWB that seems to decline with growing age (see [36]). Hence, when considering this domain of SWB, it would be particularly worthwhile to study the potential of exercise to bring about change.…”
Section: Discussionmentioning
confidence: 90%
“…However, studies have shown different gain and loss trajectories in line with the multidimensionality of SWB. For example, Kunzmann et al [36] used cross-sectional and longitudinal analyses of the two emotional components positive and negative affect to show that only negative affect fails to correlate with the age variable, whereas losses in positive affect have to be accepted with increasing age. Further analyses by these authors revealed that it is not age per se that is responsible for changes in SWB but health constraints.…”
Section: Dynamic Aspects Of Swbmentioning
confidence: 99%
“…Together these findings have been taken to suggest that the overall quality of emotional experience steadily improves during the adult life-span, at least until advanced old age during which negative affect may begin to increase and positive affect declines (e.g., Carstensen et al, 2000;Kunzmann, Little, & Smith, 2000;Kunzmann, 2008).…”
Section: Stability and Change In Affective Experience Across The Lifementioning
confidence: 94%
“…Although the evidence for age differences in positive affect is somewhat more mixed, the findings from many studies tell a similar story, namely, positive affect does not decline with age, but remains stable (Carstensen, Pasupathi, Mayr, & Nesselroade, 2000;Carstensen et al, 2011;Gross et al, 1997) or even increases (e.g., Mroczek & Kolarz, 1998). Together these findings have been taken to suggest that the overall quality of emotional experience steadily improves during the adult life-span, at least until advanced old age during which negative affect may begin to increase and positive affect declines (e.g., Carstensen et al, 2000;Kunzmann, Little, & Smith, 2000;Kunzmann, 2008).In this study, our first goal was to provide a more fine-grained analysis of age differences in negative affect by adopting a discrete emotions approach and by focussing on two distinct negative emotions: anger and sadness. A secondary goal was to analyze age differences in happiness which can be considered one facet of the broader concept of positive affect that also includes other positive emotions (e.g., pride, interest, or satisfaction).…”
mentioning
confidence: 95%
“…Note: N = 90 1 FLQM = FLQM total score; 2 Global LS = global life-satisfaction; 3 SWLS = Satisfaction with Life Scale; 4 PANAS positive = positive affect; 5 PANAS negative = negative affect; 6 EQ-5D; 7 Self-rated health VAS = Health state according to additional EQ-5D VAS scale; and 8 Age Eur J Ageing (2010) Despite decreasing functional abilities and increasing health complaints, there is empirical evidence for only very little changes in global life-satisfaction with age (Diener and Suh 1997;Kunzmann et al 2000;Schilling 2006;Smith et al 2002). In line with this so-called ''paradox of subjective well-being in old age,'' there is no connection between FLQM-score and health in terms of number of diseases with the overall score, whereas moderate correlations can be observed between FLQMscore and physical functioning (as measured by the physical subscale of the SF-36 in Study 1) and self-rated health (as measured by the EQ-5D VAS scale in Study 2), respectively.…”
Section: Overall Discussionmentioning
confidence: 99%